Home surveillance system based on LoRa backscattering - Marc Lazaro; Antonio Lazaro; Ramon Villarino; David Girbau (Scientific Reports)
Abstract This work proposes a battery-free wireless burglar alarm system based on LoRa backscattering. The system consists of multiple wireless nodes that send an alert when its sensor is triggered. The primary goal is to significantly reduce the power consumption of these wireless nodes, eliminating the need for battery replacements and maintenance associated with commercial systems. The paper addresses several crucial aspects of the application, including the hardware design of the tag, which encompasses energy management up to the RF front-end. Additionally, this paper explores the wireless communication protocol by presenting a fully analog modulation approach to optimize power consumption and system responsiveness. This novel method leverages the intrinsic frequency detection function of commercial LoRa transceivers to determine the origin of backscattered LoRa packets, thereby enabling the integration of a large number of sensors within the same frequency channel, all using a single receiver. Finally, the paper provides a proof of concept validated through on-site measurements.